Modality-specific facilitation of noninjurious sharp mechanical pain by topical capsaicin - Shabes, Polina; Rosenberger, Daniela C.; Henrich, Florian; Greffrath, Wolfgang; Treede, Rolf-Detlef; Baumgärtner, Ulf; Magerl, Walter (Pain, 2021)
We had previously shown that a “blunt blade” stimulator can mimic the noninjurious strain phase of incisional pain, but not its sustained duration. Here, we tested whether acute sensitization of the skin with topical capsaicin can add the sustained phase to this noninvasive surrogate model of intraoperative pain. Altogether, 110 healthy volunteers (55 male and 55 female; 26 ± 5 years) participated in several experiments using the “blunt blade” (0.25 × 4 mm) on normal skin (n = 36) and on skin pretreated by a high-concentration capsaicin patch (8%, Qutenza; n = 36). These data were compared with an experimental incision (n = 40) using quantitative and qualitative pain ratings by numerical rating scale and SES Pain Perception Scale descriptors. Capsaicin sensitization increased blade-induced pain magnitude and duration significantly (both P < 0.05), but it failed to fully match the sustained duration of incisional pain. In normal skin, the SES pattern of pain qualities elicited by the blade matched incision in pain magnitude and pattern of pain descriptors. In capsaicin-treated skin, the blade acquired a significant facilitation only of the perceived heat pain component (P < 0.001), but not of mechanical pain components. Thus, capsaicin morphed the descriptor pattern of the blade to become more capsaicin-like, which is probably explained best by peripheral sensitization of the TRPV1 receptor. Quantitative sensory testing in capsaicin-sensitized skin revealed hyperalgesia to heat and pressure stimuli, and loss of cold and cold pain sensitivity. These findings support our hypothesis that the blade models the early tissue-strain-related mechanical pain phase of surgical incisions.